2021
DOI: 10.1002/jcla.23931
|View full text |Cite
|
Sign up to set email alerts
|

METTL3‐mediated m6A methylation of ASPM drives hepatocellular carcinoma cells growth and metastasis

Abstract: Background Abnormal spindle‐like microcephaly (ASPM) has been proved to participate in tumor progression. However, the underlying mechanism of ASPM in liver hepatocellular carcinoma (LIHC) remains elusive. Methods The mRNA and protein expression were determined using Western blot and qRT‐PCR, and the capacities of cells proliferation, migration, and invasion were evaluated by CCK‐8, colony formation, wound healing, and transwell. MeRIP was performed to validate the interaction between ASPM and methyltransferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…For example, METTL3 synergizes with hepatitis B X-interacting protein (HBXIP) to regulate the abundance of m6A modification of hypoxia-inducible factor-1 alpha (HIF-1α), resulting in metabolic reprogramming and malignant progression of hepatocellular carcinoma cells [ 10 ]. METTL3 could also drive hepatocellular carcinoma progression by mediating m6A modification of ubiquitin-specific processing protease 7 (USP7) [ 11 ] or abnormal spindle-like microcephaly (ASPM) [ 12 ]. However, the role of METTL3 in CCA progression remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, METTL3 synergizes with hepatitis B X-interacting protein (HBXIP) to regulate the abundance of m6A modification of hypoxia-inducible factor-1 alpha (HIF-1α), resulting in metabolic reprogramming and malignant progression of hepatocellular carcinoma cells [ 10 ]. METTL3 could also drive hepatocellular carcinoma progression by mediating m6A modification of ubiquitin-specific processing protease 7 (USP7) [ 11 ] or abnormal spindle-like microcephaly (ASPM) [ 12 ]. However, the role of METTL3 in CCA progression remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that ASPM was highly expressed in hepatocellular carcinoma (HCC), and the high expression of ASPM was correlated with poor HCC prognosis. Mechanism studies showed that METTL3 promoted HCC cells growth and metastasis via m 6 A modification of ASPM ( Wang et al, 2021 ). Mettl14-mediated m 6 A played a critical role in liver regeneration by regulating the expression of polypeptide-processing proteins and maintaining endoplasmic reticulum homeostasis ( Cao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on m6A regulators in liver cancer have been performed, and the main role of m6A has been shown to be cancer promotion. METTL3 regulates the expression of the downstream targets ASPM [ 222 ] and SOCS2 [ 40 ] in a m6A-dependent manner and promotes the proliferation and metastasis of liver cancer. KIAA1429 regulates circular RNA DLC1 to promote cancer through m6A mediation [ 223 ].…”
Section: M6a and Cancersmentioning
confidence: 99%